Development of Anti-Corruption Learning through Comic Media and Anti-Corruption Poster - Abd. Syakur; Ahmad Muhibbin (Jurnal Basicedu, 2022)
This study aims to develop anti-corruption learning using comics and posters in order to instill the values of honesty and simplicity in the students of Public Junior High School Six Malang. The Research and Development (R&D) approach was used throughout this entire study. The s The participants in this study were students at Public Junior High School Six Malang . As data collection techniques, questionnaires, observations, interviews, and documentation studies are used in this study, along with focus group discussions (FGD) and field notes/logbooks. The obtained data were descriptively and qualitatively analyzed. The study's findings indicate that teachers require alternative learning that can instill the values of integrity in students, as well as anti-corruption learning media that was developed in two stages (media development and material development) and has been validated to be used as an alternative learning to instill the values of integrity, particularly honesty and simplicity. According to Article 13 of Law Number 30 of 2002, one of the prevention efforts that the KPK can carry out is to organize anti-corruption education programs at all levels of education. The material assessment on the development of anti-corruption learning with comics and posters yielded an average percentage of 88%, while the media assessment yielded an average percentage of 84%, both of which were in the good category. A conclusion can be drawn that comics and posters can be used effectively